Do Fiscal Rules Cause Fiscal Discipline Over the Electoral Cycle? - Eklou, Kodjovi (IMF Working Papers; Working Paper, 2019)
This paper estimates the causal effect of fiscal rules on political budget cycles in a sample of 67 developing countries over the period 1985-2007. We exploit the geographical pattern in the adoption of fiscal rules to isolate an exogenous source of variation in the adoption of national fiscal rules. Based on a diffusion argument, we use the number of other countries in a given subregion that have fiscal rules in place to predict the probability of having them at the country level. We find that in election years with fiscal rules in place, public consumption is reduced by 1.6 percentage point of GDP as compared to election years without these rules. This impact is equivalent to a reduction by a third of the volatility of public consumption in our sample. Furthermore, the effectiveness of these rules depends on their type, their institutional design, whether they have been in place for a long time and finally on the degree of competitiveness of elections.